Maimonides, Commentary on Hippocrates' Aphorisms : a new parallel Arabic-English edition and translation, with critical editions of the medieval Hebrew translations - Maimonides, Moses, 1135-1204, (Maimonides, Moses, 1135-1204. Medical works of Moses Maimonides., 2020)
Hippocrates' Aphorisms enjoyed great popularity in the ancient and medieval world and, according to Maimonides, it was Hippocrates' most useful work as it contained aphorisms, which every physician should know by heart. They were translated into Hebrew several times, but it was Maimonides' Commentary on Hippocrates' Aphorisms that made the work influential in Jewish circles. For the composition of his commentary, Maimonides consulted the Aphorisms through the commentary by Galen, translated by Ḥunayn ibn Isḥāq. This edition of Maimonides' Arabic commentary and its Hebrew translations, the first with an English translation based on the Arabic text, is part of a project undertaken by Gerrit Bos to critically edit Maimonides' medical works.